(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
The present article aims to historicize Vincenzo Monti’s Homeric reception in the early nineteenth-century, through the study of the genetic variants of the autograph of the Pavia lesson bearing the drafts of poetic version of Book X of the Iliad. The comparison with the eighteenth-century models of Samuel Clarke and Melchiorre Cesarotti, also in relation to the parallel and complementary "neoclassical" instances of Ugo Foscolo, is intended to add new insights for the updated chronology of the entire Monti translation, in view of the editio princeps (Brescia, Nicolò Bettoni, 1810-1811).